Vertebrate scavenging dynamics differ between carnivore and herbivore carcasses in the northern boreal forest. Issue 8 (8th August 2021) - Peers, Michael J. L.; Konkolics, Sean M.; Majchrzak, Yasmine N.; Menzies, Allyson K.; Studd, Emily K.; Boonstra, Rudy; Boutin, Stan; Lamb, Clayton T.
Abstract: Vertebrate scavenging can impact food web dynamics, but our understanding of this process stems predominantly from monitoring herbivore carrion and extrapolating results across carcass types. Recent evidence suggests carnivores may avoid intraguild scavenging to reduce parasite transmission. If this behavior is widespread across diverse ecosystems, estimation of nutrient cycling and community scavenging rates are likely biased to a currently unknown degree. We examined whether the time to initiate scavenging, carcass persistence, or the richness of species scavenging in the boreal forest of Yukon, Canada, differed between carnivore and herbivore carcasses. Vertebrates took longer to initiate scavenging on carnivore carcasses (3.2 d) relative to herbivore carcasses (1.1 d), and carnivore carcasses persisted on the landscape for over a month longer (48.4 d and 5.5 d, respectively). The longer persistence times were due to the reduction in scavenging by carnivores such as Canada lynx ( Lynx canadensis ). Decreased scavenging was caused by changes in the propensity to consume carnivore carrion, as the number of species detecting a carcass within the first week did not differ between carnivore and herbivore carcasses. These results have ramifications for our understanding of nutrient cycling and food web dynamics in the boreal forest and provide further support that carcass type should be included in future studies.